Penggunaan Restatement untuk Menjelaskan Konsep-Konsep dalam Hukum Keluarga Islam - Moch. Choirul Rizal (MAHAKIM Journal of Islamic Family Law, 2021)
Restatement can be a choice of writing method to explain legal concepts. Based on statutory regulations, doctrine and judges’ decisions, the restatement provides a comprehensive legal explanation. In Indonesia, restatements are developed and shared. Meanwhile, it becomes important to know the extent to which restatement is used by students. This research, which uses quantitative-descriptive and qualitative-descriptive approaches, found answers from students at the Islamic Family Law Study Program, Faculty of Sharia, IAIN Kediri. First, all students are still imperfect in compiling a resume using a restatement, because they do not use the judge’s decision as a source of compilation. The reason is that a softcopy of a copy of the judge’s decision regarding the concept to be explained is not available on the Decision Directory website which is managed by the Supreme Court of the Republic of Indonesia. In addition, for students who have obtained a softcopy of a copy of the judge’s decision, they are still confused about which part to use to explain a concept in Islamic family law. The percentage of students’ overall score achievement is still 62% (sixty-two percent). For that, secondly, there needs to be an effort to improve, namely through the preparation of teaching materials and socialization of how to prepare a resume using restatement strategies. The preparation of the teaching materials involved competent lecturers, judges and advocates. Third, the effort bore fruit: the resumes that the student revised were near perfection. Three authoritative sources have been used to explain a legal concept. The percentage of students’ overall grade achievement increased by 27% (twenty-seven percent), so that it became 90% (ninety percent).